Transformasi Paradigma Literatur Ulumul Quran dan Ulumul Hadis di Indonesia - Rifqi Muhammad Fatkhi; Eva Nugraha (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
This article analyzes the transformation of paradigms in the literature of Ulumul Quran and Ulumul Hadis in Indonesia. The study employs historical, discourse analysis, and al-Jabiri’s reading theory to explore the construction and dynamics of these disciplines. The findings reveal that the study of Ulumul Quran and Ulumul Hadis in Indonesia experienced stagnation until the late 20th century, with most literature being reiterations of Middle Eastern scholars’ works. However, the post-1990s era marked a paradigm shift influenced by Western thought and modern approaches such as phenomenology and hermeneutics. This study recommends interdisciplinary methods to enhance the relevance of these fields in Indonesia's contemporary socio-cultural context. Additionally, Living Quran and Living Hadis studies are proposed as new research directions to explore the social and religious dimensions of Islamic texts.